Prevalence of Anti-HCV Seropositivity among Dialysis Patients in Bangladesh - Chakrabarty, Ashish Kumar; Mamun, Aiyub Al; Swapnil, Mamun Al Mahtab; Tarafdar, Arun Joyoti (The Planet, 2023)
Background: HCV is the primary cause of acute andchronic hepatitis, liver cirrhosis, hepatocellular carcinoma,and related fatalities. HCV transmission in industrializednations is associated with drug use, while healthcareassociated transmission is the primary mode of transmissionin underdeveloped nations. Risk factors for dialysis patientsinclude transfusions, dialysis duration, IV drug use, andkidney transplant history. Objective: This study aimed toestablish the prevalence of HCV in HD patients inBangladesh and identify the primary risk factors for virustransmission among this population. Methods: From July2021 to June 2022, 380 patients at BIRDEM hospital andBSMMU in Dhaka, Bangladesh were studied crosssectionally. Adults were studied. For proper data collectionand interpretation, hemodialys is patients completed athorough multiple-choice questionnaire. 5 ml of blood was collected in tubes, clotted at roomtemperature, and centrifuged. Serum anti-HCV ELISA testing followed. Rapid anti-HCV kitlevels were measured. Results: There was no significant association between Anti-HCVseropositivity and age or gender, with odds ratios of 1.0 and p-values of 0.624 and 0.963,respectively. There were significant associations with risk factors including a history ofjaundice, previous surgeries, circumcision in males, needle-stick injuries, ear-nose-bodypiercing in females, and visiting a community barber for shaving in males. No significantcorrelation was found between visiting unregistered healthcare facilities (OR 0.9; p=0.098). Conclusion: This study suggests a noteworthy occurrence of anti-HCV sero-positivity amonghemodialysis patients in Dhaka. Diverse lifestyles increase the likelihood of testing positive foranti-HCV.